Adaptation and control circuits in bacterial chemotaxis. (24th September 2010) - Roberts, Mark A.J.; Papachristodoulou, Antonis; Armitage, Judith P.
Abstract : Bacteria are capable of sensing and responding to changes in their environment. One of the ways they do this is via chemotaxis, regulating swimming behaviour. The chemotaxis pathway senses chemoattractant gradients and uses a feedback loop to change the bacterial swimming pattern; this feedback loop differs in detail between species. In the present article, we summarize the current understanding of the regulatory mechanisms in three species and how these pathways can be viewed and analysed through the ideas of feedback control systems engineering.